Two new species of the sharpshooter genus Paratubana (Hemiptera: Cicadellidae: Cicadellini) from alpine fields of Rio de Janeiro state, southeastern Brazil - Côrte, Isabele; Pecly, Nathalia H.; Quintas, Victor; Ferreira, André L. D.; Cavichioli, Rodney R.; Mejdalani, Gabriel (Zootaxa, 2021)
Two new species of Paratubana Young, 1977 are described and illustrated from Rio de Janeiro state, southeastern Brazil, based on specimens collected in alpine fields (above 1,800 m) of the Serra dos Órgãos mountain range. Paratubana auromarginata sp. nov. (Pico da Caledônia) can be recognized by the paraphyses with the apex bifurcate, forming an outer subquadrate projection and inner spiniform process, whereas in P. takiyae sp. nov. (Parque Nacional da Serra dos Órgãos) the paraphyses have a pair of strong spiniform processes directed dorsally and crossing each other. The two new species are apparently closely related to each other and both use Eryngium L. (Apiaceae) as host plants. A key to males of the ten known species of the genus is added, as well as two maps of their known distribution.